Preparation of betaine‐modified cationic cellulose and its application in the treatment of reactive dye wastewater. Issue 15 (18th February 2014) - Ma, Wei; Yan, Shumin; Meng, Mei; Zhang, Shufen
ABSTRACT Betaine‐modified cationic cellulose was prepared through the reaction of cellulose with betaine hydrochloride by an efficient one‐step dry method. Dicyandiamide was used as a dehydrating agent to promote the formation of ester bonds between the reactants. Fourier transform infrared spectroscopy, X‐ray diffraction, and scanning electron microscopy were used to characterize the cellulose betainate. Experiments showed that at a molar ratio of the cellulose glucose unit, betaine hydrochloride to dicyandiamide, of 1:1:0.5 at 150°C for 3 h, the degree of substitution of the cationic group reached 0.80. The adsorption of simulated C. I. Reactive Red 24 and C. I. Reactive Red 195 wastewater on the cationic cellulose was carried out, and the effects of the adsorbent dose, initial dye concentration, and salt concentration on the dye removal efficiency were investigated. The equilibrium adsorption isotherm data of the cationic cellulose exhibited a better fit to the Langmuir isotherm model than the Freundlich one. The experimental results suggest that the prepared cationic cellulose materials show potential application for reactive dye wastewater treatment. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40522.